“I felt I should be there, all these people talking on my behalf without consulting me”: Gender, Experience and Expertise in the Irish Mixed Economy of Welfare, 1970–1990s - Earner-Byrne, Lindsey (Historein, 2024)
In the early 1970s, Cherish, the first support and advocacy group for unmarried mothers run by unmarried mothers, emerged into the mixed economy of welfare in the Irish Republic. The self-help aspect of the organisation was fundamental to its sociopolitical agenda to remove the stigma associated with unmarried motherhood and the legal status of illegitimacy, to secure welfare payments for this group and to reframe Irish understandings of what constituted a legitimate family. This article explores how Cherish reflected and contributed to a particular moment in Irish gender and welfare history, when notions of responsibility, the role of religion and the state were being redefined. It reveals how the organisation engaged with and reshaped the existing mixed economy of welfare by reframing understandings of expertise, challenging inherent moral biases, and broadening the concept of family.